The behaviour of sharks in captivity - Hussain, Syed Makhdoom (Indian Journal of Fisheries, 2011)
Six species of sharks, viz. Engomphodus taurus (sand tiger), Ginglymostoma cirratum (nurse shark), Negoprion brtvirostris (lemon sharks), Carcharhinus plumbeus (sand bar), C. limbatus (Pacific black tip), and C. leucas (bull shark), were selected to understand some patterns of shark’s behaviour. The general behavioural patterns like follows, circles and give ways were commonly noted among all the 6 species; however, each species was found to differ from the other. Locomotion in shirk was found to be a combination of anguilliform and crangidform modes. Swimming speed for 6 sharks was measured as distance (cm) travelled per second. Black tip sharks showed highest speed while sand tigers were found to exhibit lowest speed.